Pengaruh Jenis Bunga Dan Waktu Pemetikan Terhadap Sifat Fisikokimia dan Aktivitas Antibakteri Minyak Atsiri Bunga Kenanga (Cananga odorata) - Yuliani Aisyah; Sri Haryani; Rulita Maulidya (Agricultural Faculty, 2016)
Essential oil is oil produced from plant extracts which is volatile at room temperature and has a unique fragrant smell as such its plant source. Cananga flower produces essential oil. This oil has antibacterial properties since it contains karyophyllene. This kind of oil was extracted by using steam and water method. Antibacterial test was conducted against Staphylococcus aureus and Escherichia coli by using disc diffusion method with 200 uL concentration. The research design used a randomized block design (RBD) with factorial pattern containing two factors. The first factor was type of flower (Cananga) (J) with three levels, namely J1 = big flower, J2 = small flower, J3 = combination of big and small flowers. The second factor was picking time (W) with two levels; W1 = in the morning, and W2 = in the evening. Combination treatment in this study was 2 × 3 = 6 (six) treatments with three (3) repetitions, thus obtained 18 experimental units. The results showed that the type of flower and picking time had no correlation to the yield, density, refractive index, but they revealed interaction or significant effect on the antibacterial test.